Significance of Public Revenue in Odisha State Finances: An Analytical Study - Pragnya Laxmi Padhi, Dr. Umakanta Tripathy (International Journal of Advanced Science and Technology, 2020)
Public revenue is one of the major components of State finance. Generally, tax revenue and non-tax revenue are considered as the sources of government revenue. However the government collects revenue from various sources and spends on various sectors of the economy for macroeconomic stabilization and augment the economic development. This Paper mainly focuses on significance of public revenue of Odisha state finances from 2000-01 to 2016-17. It explains the composition of revenue receipts, own tax revenue and own non tax revenue and its % of GSDP. It measures the significance of growth performance of the state’s public revenue by using Semi log model of Regression analysis. Given such a scenario, the study has conformed to the alternative hypothesis that own tax revenue and own non tax revenue are in the differential with positive growth rate of Odisha state finances over the study period.